A novel technique for detecting the misbehavior nodes in wireless adhoc networks - Narayanan, Kumar; Anandan, R; Paul Chinnaraju, Swaraj; Manikandan, A (International Journal of Engineering and Technology, 2018)
Wireless adhoc network acts as the most emerging platform in the current trend that plays a vital role in the field of sensing, analyzing the network route, rectifying the problem within the network. This also pays route for many advanced studies. Observing aid depletion attacks on the routing layers is the main objective of this paper. It also attempts to entirely disable community nodes by draining their battery strength immediately. Such an attempt to drain their battery strength is said to be as depletion attack, and these attacks are not specific to any particular protocol. Under the worst case, even a single depletion can empower a community-wide usage by O(N), where N is the total number of network nodes used.Â Â